Comparison of the yield and properties of bio-oil produced by slow and fast pyrolysis of rice husks and coconut shells - Gu, Mandy Su Zan; Jourabchi, Seyed Amirmostafa; Ng, Hoon Kiat; Gan, Suyin (Trans Tech Publications Ltd, 2014)
Slow pyrolysis (SP) and fast pyrolysis (FP) of rice husks, coconut shells and their mixtures were studied in a fixed bed reactor. The objectives of this study were to compare the yields and properties of bio-oils produced using SP and FP methods within a pyrolysis temperature range of 400˚C to 600˚C. Three different biomass compositions, 100% rice husks (RH), 100% coconut shells (CS) and a mixture of 50% rice husks with 50% of coconut shells (RH50/CS50) were experimented. In SP, the maximum yield of bio-oil for RH, CS and RH50/CS50 were 45.45%, 37.01%, 38.29% at temperatures of 550˚C, 500˚C and 600˚C respectively. As for FP, the maximum bio-oil yield obtained for RH, CS and RH50/CS50 were 50.52%, 40.14% and 42.25% at temperatures of 500˚C, 600˚C and 550˚C respectively. At these optimum pyrolysis temperatures, the percentage differences in bio oil yields for SP and FP were 10.57%, 8.11% and 9.83% for RH, CS and RH50/CS50 respectively. Based on American Society for Testing and Materials (ASTM) standard procedures, the properties of bio-oil were characterised and it was found that the bio oil produced by FP at optimum temperatures were less acidic, higher density, lower water content and viscosity as compared to the bio-oil produced by SP method for all biomass compositions